Factors Affecting Teacher-Candidates' Practicum Evaluations - Edwin Ralph (University of Windsor, 2006)
This report is an extension of a study that examined the final evaluations of 17 cohorts of teacher-candidates (n=374), who completed their 16-week extended-practicum through one Western Canadian university in one of the years from 1986 to 2002. Evaluation results based on nine instructional categories were analyzed according to four factors: (a) grade level taught; (b) school location; (c) year of the internship; and (d) gender of the intern. Descriptive statistics calculated for each of these four factors revealed minor differences in the intern sub-groups' aggregates of final evaluation ratings. For grade level, interns who taught K-3 were rated slightly higher than those in the other grade levels in six of the nine instructional skills. The interns who taught grade 7-12 were rated lowest of the three groups in three of the teaching categories. With respect to urban/rural school location of the internship, interns from rural schools were evaluated slightly higher than their urban counterparts for six of the nine skills. For year of the practicum, calculations showed slightly better evaluations in three teaching skills for interns who completed the practicum after 1996, than for those who completed it during the 1986-1995 period. Female interns were rated slightly higher in eight of the nine teaching categories than were their male colleagues. Possible explanations accounting for these minor differences are provided, and implications discussed for the program under study and for their "transferability" (Donmoyer, 1990) to pre-service teacher preparation programs.